Assessment of oral hypoglycaemic activity of water soluble extract of aloe vera and its interaction with glipizide in alloxan induced diabetic Wistar Rats - Tiwari, Vikalp; Gudsurkar, Gopal (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Assessment of oral hypoglycaemic activity of water soluble extract of Aloe vera and its interaction with Glipizide in Alloxan induced diabetic Wistar rats. Methods: Under standard condition of testing, alloxan induced diabetic rats were kept in fasting state of 8 hours and then glucose in dose of 1gm/kg was given PO by feeding tube. There after water soluble extract of aloe vera in dose of 200mg/kg BW dissolves in 1ml of Distilled water (DW) to test group 1, Glipizide in dose of 2.5mg/kg BW dissolved in 1ml DW was given to standard group. Test group 2 received combination of Aloe vera 200mg/kg BW and Glipizide in dose of 2.5mg/kg BW dissolved in 1ml Dw. Control group received 1ml of Distilled water. Blood sugars levels of all Rats in each group were checked with Glucometer. Results: Clinically and statistically significant glucose lowering effect was observed in groups administered with Aloe vera and better results were observed in group receiving Aloe vera and Glipizide combination. Conclusions: Water soluble extract of aloe vera has significant hypoglycaemic activity and the results showed that co-administration of Aloe vera and Glipizide has superior hypoglycaemic activity compared to Aloe vera and Glipizide given Individually.